Metal–Organic‐Framework‐Derived Co3S4 Hollow Nanoboxes for the Selective Reduction of Nitroarenes. Issue 18 (21st August 2018) - Yang, Shuliang; Peng, Li; Sun, Daniel T.; Oveisi, Emad; Bulut, Safak; Queen, Wendy L.
Abstract: MOF‐derived Co3 S4 /CN hollow nanoboxes (CN=nitrogen‐doped carbon) was used to catalyze the chemoselective reduction of nitroarenes to anilines under mild reaction conditions with H2 as the reducing agent. The catalyst provides high conversion efficiencies and selectivities for a variety of nitroarene substrates that contain electron‐donating or electron‐withdrawing substituents under mild reaction conditions (in methanol at 60 °C). Further, the nanobox inhibits both dehalogenation and vinyl hydrogenation reactions, which are common limitations of state‐of‐the‐art Pd‐based catalysts. Because the reactions result in pure aniline products, the need for separation by column chromatography is eliminated. The resulting anilines are easily separated from the methanolic reaction solution in just three simple steps (centrifugation, decantation, and drying). If employed in industrial processes, catalysts of this kind would significantly reduce the amount of waste organic solvent generated and thus satisfy the need for sustainable chemical processes. Abstract : Nanocatalysts go hollow : MOF‐derived Co3 S4 /nitrogen‐doped carbon hollow nanoboxes catalyze the chemoselective reduction of nitroarenes to anilines with excellent conversion and selectivity by using H2 as hydrogen source. The pure aniline products require no additional purification processes and are easily separated from the reaction solution in just three simple steps, and thus the amount of waste organic solvent generated is efficiently reduced.